2020
DOI: 10.1088/1755-1315/433/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the operation of a combine harvester with an additional sieve with adjustable holes for sunflower harvesting

Abstract: The cost of production of sunflower is determined by the number of operations for its cultivation as well as the manufacturing charges for them. The extraneous matter content of the hopper sunflower heap is the factor that can increase the cost of sunflower production. In connection with that, it is advisable to reach the minimum values of the extraneous matter content in the hopper heap during sunflower harvesting. The article substantiates the design of the sieve with additional holes which is installed as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Higher values were found by Stefanoni et al (2020) and Sintim et al (2016) which found 7.82 and 11.70% w/w, respectively [39,40]. In other herbaceous oil crops, seed loss ranges from 1% as in sunflower [62,63] or in canola [64,65], and 3% as in safflower [33], or even higher as in castor bean harvesting [33]. However, such information only provides evidence regarding the total amount of seed loss, but it fails in pointing out what is responsible for that loss.…”
Section: Seed Loss Evaluationmentioning
confidence: 76%
“…Higher values were found by Stefanoni et al (2020) and Sintim et al (2016) which found 7.82 and 11.70% w/w, respectively [39,40]. In other herbaceous oil crops, seed loss ranges from 1% as in sunflower [62,63] or in canola [64,65], and 3% as in safflower [33], or even higher as in castor bean harvesting [33]. However, such information only provides evidence regarding the total amount of seed loss, but it fails in pointing out what is responsible for that loss.…”
Section: Seed Loss Evaluationmentioning
confidence: 76%
“…TITLE-ABS-KEY ("sunflower" AND "harvest *") 1020 773 7 [34][35][36][37][38][39][40] TITLE-ABS-KEY ("Heliantus annuus" AND "harvest *") 427 323 TITLE-ABS-KEY ("canola" AND "harvest *") 633 380…”
Section: -2020 Papers Actually Dealing With Mechanical Harvestingmentioning
confidence: 99%
“…Those sieve holes were longitudinally shaped, just like sunflower seeds, and they also permitted the adjustment the area according the characteristics of the seeds of cultivar harvested. Such improvements permitted the significant reduction of extraneous material in the hopper heap by 38-42% by weight, in comparison with a combine harvester not equipped with such particular sieve [39].…”
Section: Sunflower Mechanical Harvestingmentioning
confidence: 99%
“…For example, the Helianthus 12000 series sunflower header developed by the company Capello in Italy (Capello Srl, Via Valle Po, 10012100 Cuneo, Italy), the Falcon series sunflower header developed by the company Rostselmash in Russia (Rostselmash, Rostov Nadon, Rostov Oblast, Russia), the G3 series sunflower header developed by the company Fantini in Italy and the ZIECLER series sunflower header developed by the company Dragotec in Germany (Dragotec International GmbH, Hub 7, 84329 Wurmannsquick, Germany.) are based on the principle of a corn header [13][14][15][16]. At present, the research on the harvesting of sunflower is still in its infancy in China.…”
Section: Introductionmentioning
confidence: 99%